HAK NON MUSLIM DALAM HUKUM KEWARISAN ISLAM PERSPEKTIF MAQASID SYARIAH (Telaah Putusan Pengadilan Agama Kabanjahe Nomor: 2/Pdt.G/2011/PA-Kbj) - setyawan, rahmad (Program Studi Hukum Keluarga Islam, 2025)
This article discusses non-Muslim rights in Islamic inheritance law with a case study of the Kabanjahe Religious Court decision number: 2/Pdt.G/2011/PA-Kbj. Methodologically, this research is a literature research with descriptive analytical method. The results of the study indicate a shift in the stelsel of Islamic inheritance law from the Qur'an and hadith into modern Indonesian fiqh. Normatively, the provisions of Islamic inheritance law and the Compilation of Islamic Law (KHI) explain that religious differences between the testator and the heirs are a barrier to inheriting each other. However, as stated in the decision of the Kabanjahe Religious Court number: 2/Pdt.G/2011/PA-Kbj, non Muslim heirs can be given a share of the assets of a Muslim heir through the construction of a mandatory will in order to realize public benefits oriented towards a sense of justice. Essentially, the decision underlines the importance of understanding Islamic inheritance law not only textually, but also contextually by taking into account social realities and inter-religious relations. In addition, from the perspective of maqasid sharia, the granting of mandatory wills to non Muslim heirs can also maintain or protect the five main interests in Islam, namely religion, soul, mind, descendants, and property. Keywords: Non Muslim Rights, Mandatory Will, Maqasid Sharia.